Prophylactic Modulation of Methane and Nitrous Oxide Emitted from Ruminants Livestock for Sustainable Animal Agriculture (REVIEW) - J Takahashi (Media Peternakan, 2014)
Major greenhouse gases (GHG) attributed to animal agriculture sector are methane (CH4) and nitrous oxide (N2O), either generated from enteric fermentation or manure. The abatement mechanism of rumen CH4 emission may be divided to direct and indirect suppression to methanogens in the rumen.The most significant strategy to mitigate ruminal CH4 emission in indirect manner is to promote alternative metabolic pathway to dispose of the reducing power, competing with methanogenesis for H2 uptake. This includes prebiotics and probiotics (mostly propionate enhancers) which consume metabolic hydrogen (H2) compete with methanogens and abate rumen methanogenesis in indirect manner. With regard to mitigate GHG emissions from manure, such waste has been proposed as a renewable energy and nitrogen sources through biogas plant. Furthermore, in advanced new biogas system, the ammonia stripping from digested slurry of livestock manure in biogas plant has been examined to apply to nitrogen recycling-options mitigating N2O emission. These options are: (1) ammonolysis on fiber-rich feedstuffs, (2) saccharification of the NH3 treated cellulose biomass to produce bio-ethanol, and (3) reformed hydrogen into NH3 fuel cell to generate electricity with proton exchange membrane fuel cell (PEM).Key words: rumen methane, nitrous oxide, probiotics, prebiotics, ammonia stripping